Luminescent studies of binuclear ternary europium(III) pyridineoxide tetrazolate complexes containing bis‐phosphine oxide as auxiliary co‐ligands. (27th November 2017) - Mal, Suraj; Pietraszkiewicz, Marek; Pietraszkiewicz, Oksana
Abstract: A new class of antenna chromophores so called 'tetrazolates' have not been explored much for lanthanide luminescencent complexes. However, we have already published several articles considering pyridineoxide tetrazolates as sensitizer with lanthanide ions. Although this class of antenna attracted much less attention because of its poor photoluminescence quantum yields (tris‐pyridineoxide tetrazolate europium complex = 13% in solution) we tried and successfully achieved to improve the photoluminescence quantum yields for this particular antenna molecule by replacing coordinated water from the inner coordination sphere of europium ion by introducing phosphine oxides as additional chromophore. In the present article the two bis‐phosphine oxides attach two molecules of tris‐pyridineoxide tetrazolate europium(III) complex which leads to the improvement of the overall molar absorption coefficients as well as photo‐physical properties of the complexes. We found more than two‐fold increase (31% in solution) in photoluminescence quantum yield with one of the coordinated phosphine oxides comparing with that of tris‐pyridineoxide tetrazolate europium(III) complex.